Eigenvalues of the matching derangement graph - Ku, Cheng Yeaw (Springer Verlag, 2018)
In this paper, we derive a formula for the eigenvalues of the matching derangement graph. The formula gives an insight regarding the alternating sign conjecture for the eigenvalues of the matching derangement graph. In particular, we show that the alternating sign property holds for certain partitions.